Analysis of choroidal thickness, macular thickness, peripapillary retinal nerve fiber layer thickness, and macular vascular density in children with unilateral amblyopia using swept-source optical coherence tomography and their changes following occlusion therapy - Shrutika Bhimewar; V. Kavitha; M. Heralgi Mallikarjun; B. K. Pradeep Sagar (Taiwan Journal of Ophthalmology)
PURPOSE: The purpose of this study was to analyze choroidal thickness (CT), along with macular thickness (MT), peripapillary retinal nerve fiber layer thickness (RNFLT), and macular vascular density (MVD) using swept-source optical coherence tomography (SS-OCT) in children with unilateral amblyopia, and compare the same with normal fellow eyes and normal eyes of normal children before and following occlusion therapy. MATERIALS AND METHODS: This was a prospective, longitudinal study of 60 children (4-18 years); 30 children had unilateral amblyopia and remaining 30 were normal. Group 1 consisted of 30 amblyopic eyes of children with unilateral amblyopia; Group 2 consisted of 30 fellow normal eyes of Group 1; Group 3 consisted of normal eyes of normal children. Best-corrected visual acuity (BCVA) using logarithmic minimum angle of resolution (LogMAR) chart, detailed ophthalmic examination, SS-OCT for CT, MT, RNFLT, and MVD at the level of superficial, deep, and choriocapillary plexus in both eyes were assessed at presentation, third, sixth and 12th month follow-up. In Group 1, spectacles (at presentation) and occlusion therapy (1 month) were advised. RESULTS: In Group 1, the mean CT and MT were higher whereas LogMAR BCVA and MVD were lower than Groups 2 and 3 at presentation. In Group 1, post occlusion therapy, the mean CT and MT decreased whereas LogMAR BCVA and MVD increased. There was no significant change in RNFLT in Group 1 as compared to Groups 2 and 3, pre- and post occlusion therapy. CONCLUSION: CT and MT in amblyopic eyes were significantly higher. Following occlusion therapy, CT decreased in each follow-up but was not significant whereas MT decreased significantly at the last follow-up visit. There was no difference in RNFLT in amblyopic eyes as compared with normal fellow eyes and control eyes before and after occlusion therapy. MVD was lower in amblyopic eyes and increased during follow-up visits but was not significant.